Cardiac decompensation of patients before transcatheter aortic valve implantation—clinical presentation, responsiveness to associated medication, and prognosis - Fischer-Rasokat, Ulrich; Renker, Matthias; Charitos, Efstratios I.; Strunk, Christopher; Treiber, Julia; Rolf, Andreas; Weferling, Maren; Choi, Yeong-Hoon; Hamm, Christian W.; Kim, Won-Keun (Frontiers in Cardiovascular Medicine, 2023)
Aims Cardiac decompensation (CD) in patients with aortic stenosis is a “red flag” for future adverse events. We classified patients undergoing transcatheter aortic valve implantation (TAVI) into those with acute, prior, or no prior CD at the timepoint of TAVI and compared their clinical presentation, prognosis, and effects of the prescribed medication during follow-up. Methods Retrospective analysis of patients of one center fulfilling the criteria of 30-day device success after transfemoral TAVI. Results From those patients with no CD (n = 1,985) ranging to those with prior CD (n = 497) and to those with acute CD (n = 87), we observed a stepwise increase in the proportion of patients in poor clinical condition, NYHA class III/IV, low psoas muscle area, fluid overload (rales, oedema, pleural effusion), reduced ejection fraction, renal insufficiency, and anemia. More diuretics but less renin-angiotensin system inhibitors (ACEI/ARB) were prescribed for patients with acute CD compared to other groups. Prior CD (hazard ratio and 95% CI 1.40; 1.02–1.91) and acute CD (1.72; 1.01–2.91), a reduced general condition (1.53; 1.06–2.20), fluid overload (1.54;1.14–2.08), atrial fibrillation (1.76; 1.32–2.33), and anemia (1.43;1.08–1.89) emerged as strong independent predictors of one-year mortality. In all three classes of CD, prescribing of ACEI/ARB was associated with a substantial improvement of survival. Conclusions The clinical presentation of (acute or prior) cardiac decompensation in patients with AS overlapped substantially with that of patients with classical signs of heart failure. Our results may support an early treatment strategy in patients with left ventricular dysfuntion before clinical signs of congestion are manifest. Moreover, these patients require intensive medical attention after TAVI.